Fenomena Tradisi Megengan di Tulungagung - Kutbuddin Aibak (Millah: Journal of Religious Studies, 2010)
The study is a qualitative research with phenomenological approach. It explored the phenomena of megengan tradition in Sumbergempol Tulungagung, and especially conducted in three villages, i.e. Bendiljati Kulon, Sambijajar, and Tambakrejo. The findings show that; first, megengan tradition is only executed on the last ten days of Sya’ban /Ruwah month. On the last development, megengan tradition has moved into various forms and ways, as shown in the megengan tradition occurred in Sumbergempol Tulungagung. Second, the tradition has been changing in its forms such as its time, place, volume, and funeral visit tradition.